Academic Career Development among State Universities and Colleges (SUCs) in Samar - Refuncion , Jose Marlon Jr. (Journal of Interdisciplinary Perspectives, 2024)
The study sought to answer the extent of implementation of the career development program and the significant relationship between the faculty profiles and the career development programs and processes. The study also wanted to know the challenges and strategies of career development by using a mixed-method research design and randomly picking 125 faculty respondents from different State Universities and Colleges on Samar Island. It was revealed that the lowest career development program extent of implementation was career development counseling and career development coaching and mentoring which both indicated “Moderately Implemented”. It was also shown in the study that there is a significant correlation between career advancement educational background, academic rank, and the number of published research of the faculty. There is also a significant relationship between career development training to international, national, and local training provided and attended. The career development support process has also a significant relationship with the training of faculty internationally and lastly, career development counseling is significantly related to the number of published research. Thematic analysis was also used for providing career development challenges and strategies and it was discovered that the faculty were challenged with three reasons as follows: (1) there are many tasks in Publishing Research; (2) Financial struggle in finishing a Doctorate Degree; and (3) Time constraints because of designation. Subsequently, the career development strategies also revealed the following: (1) Faculty must finish a doctorate to meet the educational requirement; (2) Conduct and publish research to maximize higher possible points; and (3) Study the guidelines of NBC 461 to achieve higher academic rank. Faculty facing challenges in career development makes them initiate self-development in keeping up points in consonance with the NBC provisions and policies, some are still in adjustment to have a culture of research, challenged by finances both education and personal, a problem of which balancing is tough. Encouraging SUC to help faculty career growth and develop a model that effectively does both individual and institutional support. With the results from the research conducted, quantitative and qualitative approaches, and recommendations the researcher generated a model of academic career development which is called “Refuncion’s Academic Career Development Model.”